Leans Illusion in Hexapod Simulator Facilitates Erroneous Responses to Artificial Horizon in Airline Pilots. (September 2022) - van den Hoed, Annemarie; Landman, Annemarie; Van Baelen, Dirk; Stroosma, Olaf; van Paassen, M. M. (René); Groen, Eric L.; Mulder, Max
Objective: We tested whether a procedure in a hexapod simulator can cause incorrect assumptions of the bank angle (i.e., the "leans") in airline pilots as well as incorrect interpretations of the attitude indicator (AI). Background: The effect of the leans on interpretation errors has previously been demonstrated in nonpilots. In-flight, incorrect assumptions can arise due to misleading roll cues (spatial disorientation). Method: Pilots ( n = 18) performed 36 runs, in which they were asked to roll to wings level using only the AI. They received roll cues before the AI was shown, which matched with the AI bank angle direction in most runs, but which were toward the opposite direction in a leans-opposite condition (four runs). In a baseline condition (four runs), they received no roll cues. To test whether pilots responded to the AI, the AI sometimes showed wings level following roll cues in a leans-level condition (four runs). Results: Overall, pilots made significantly more errors in the leans-opposite (19.4%) compared to the baseline (6.9%) or leans-level condition (0.0%). There was a pronounced learning effect in the leans-opposite condition, as 38.9% of pilots made an error in the first exposure to this condition. Experience (i.e., flight hours) had no significant effects. Conclusion: The leans procedure was effective in inducing AI misinterpretations and control input errors in pilots. Application: The procedure can be used in spatial disorientation demonstrations. The results underline the importance of unambiguous displays that should be able to quickly correct incorrect assumptions due to spatial disorientation.